Financial analysis of educational institutions listed on the US stock market (Journal of Economic Research & Business Administration, 2025)
This paper examines the financial indicators of educational organizations whose shares are traded on the US stock market. The study aims to analyze private educational companies focused on online learning and technological educational services. The study's main objective is to analyze these organizations' key financial indicators and determine their investment attractiveness and sustainability. The methodological basis includes observation, classification, statistical analysis, and comparative analysis of market indicators. The study examines capitalization, beta coefficient, dividend yield, profitability, and liquidity indicators of 43 educational companies listed on the NYSE, NASDAQ, and AMEX. The data was collected from financial platforms and then classified and analyzed by key financial metrics.The results show that most companies are classified as Nano-cap, indicating high volatility and investment risks. More than 80% of the companies do not pay dividends. The share of loss-making companies has decreased over the past 5 years, but there remains a significant spread in profitability indicators. Financial stability varies: there is both high return on equity in some companies and low liquidity in others, which increases the risk of insolvency.The value of the study lies in the comprehensive analysis of educational organizations in the context of the stock market, which has not previously received sufficient coverage in the scientific literature. The results obtained may be useful for investors in assessing the risks and investment opportunities in this sector.Key words: Educational organizations, stock market, indicators.